Electric Power Systems - Weedy B. M.; Cory B. J.; Jenkins N.; Ekanayake J. B.; Strbac G. (Chichester, John Wiley & Sons, Ltd., 2012)
Electric power systems are going through a period of dramatic change with the need to reduce environmental impact, provide a secure supply of power to an increasing world population while aging infrastructure and equipment in many established systems needs replacing. Today's student has to understand both the large amount of plant and equipment that is in use as well as the possibilities offered by new technologies. Now comprehensively updated and revised, the fifth edition of this classic textbook provides a modern foundation in power systems engineering. The emphasis on practical analysis, modelling and fundamental principles, so successful in previous editions, is retained together with broad coverage of the subject while avoiding complex mathematics. Throughout, the worked examples and computer simulations used to explain concepts and calculation techniques have been modernised, as have all figures.Features of the fifth edition: